RECONSTRUCTION OF THE REALITY IN THE CONTEMPORARY ART PHOTOGRAPHY: STAGED PHOTOGRAPHY - Tuna UYSAL (Ulakbilge: Sosyal Bilimler Dergisi, 2017)
With the affects of post-war art movements like avant-garde, conceptual, abstract etc. art of photography pursued a research after the new communication skills, likewise the other disciplines. In this research period, especially in the postmodern era, art of photography pursued a strategy like not to tell the truth but reconstruct it. As it has done in its early times, the art of photography started to search its references from other disciplines. In the postmodern era, the art of photography took its references from painting, literature, theatre or mythology -as it done beforeas well as mass media culture like cinema, press, television. Art of photography do not aim to preserve its prestigious place in the scene of art by reconstructing the truth. It’s first aim to study its theme by the means of “reality” which is always accepted without prejudice by its viewer. The other important aim is, to start a new kind of questioning which becomes possible by the skills of other contemporary communication languages.